Mitigation of electroencephalographic and cardiovascular responses to castration in Bos indicus bulls following the administration of either lidocaine or meloxicam. (November 2017) - Lehmann, Heidi S.; Musk, Gabrielle C.; Laurence, Michael; Hyndman, Timothy H.; Tuke, Jonathan; Collins, Teresa; Gleerup, Karina B.; Johnson, Craig B.
Abstract: Objective: To investigate the mitigating effects of administration of local anaesthetic or systemic meloxicam on the electroencephalographic (EEG) and cardiovascular responses during surgical castration of Bos indicus bull calves. Study design: Prospective, randomized, experimental study. Animals: Thirty-six 6–8 month-old Bos indicus bull calves, with a mean ± standard deviation weight of 237 ± 19 kg. Methods: Animals were allocated randomly to three groups of 12 (group L, 260 mg of 2% lidocaine subcutaneously and intratesticularly 5 minutes prior to castration; group M, 0.5 mg kg −1 of meloxicam subcutaneously 30 minutes prior to castration; group C, no preoperative analgesia administered). Anaesthesia was induced and maintained with halothane (0.9–1.1%) in oxygen. Electroencephalogram, heart rate (HR) and mean blood pressure (MAP) were recorded for 300 seconds prior to (baseline, B) and from the start of surgery (first testicle removal, T1). HR and MAP were compared at 10 second intervals for 90 seconds from the start of T1. Median frequency ( F 50 ), spectral edge frequency ( F 95 ) and total power of the EEG ( P tot ) were analysed using area under the curve comparing T1 to B. Results: All EEG variables were significantly different between B and T1 ( p ≤ 0.0001). No differences in F 50 were found between groups during T1 ( p  = 0.6491). F 95 and P tot were significantly different between group L and groups C and M during T1 ( p  = 0.0005 and 0.0163, respectively). There were transient significant changes in HR and MAP in groups L and M compared to group C during the 20–50 second periods. Conclusions: The EEG changes indicate nociceptive responses in all three groups during surgical castration, greater in group L compared to groups C and M. Both analgesics attenuated the peracute cardiovascular response. Lidocaine and meloxicam administered prior to castration attenuated these responses in Bos indicus bull calves. Clinical relevance: These findings provide support for the preoperative administration of lidocaine and potentially meloxicam for castration in Bos indicus bull calves.